Penentuan Efek Ekstrak Etanol Buah Sawo Muda (Manilkara zapota L.) Untuk Mengobati Luka Bakar Pada Marmut Jantan - Muhajri Agusfina; Fauzan Syah (Program Studi DIII Farmasi Akademi Farmasi Dwi Farma, 2021)
A research has been carried out on determining the effect of young sapodilla fruit (Manilkara zapota L.) ethanol extract to treat burns in male guinea pigs with the observed parameters including wound length. From the statistical tests that have been carried out, it results that the data is normally distributed which is calculated using the Barlet test. Whereas the ANAVA test showed no clear difference in healing between the test substance groups at 5% concentration, 10% concentration, and 20% concentration